1996
DOI: 10.1128/mcb.16.11.5997
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of α1b Adrenergic Receptors (α1bAR) by Nuclear Factor 1 (NF1): a Decline in the Concentration of NF1 Correlates with the Downregulation of α1bAR Gene Expression in Regenerating Liver

Abstract: The 5 upstream region from ؊490 to ؊540 (footprint II) within the dominant P2 promoter of the rat ␣ 1b adrenergic receptor (␣ 1b AR) gene is recognized by a sequence-specific DNA-binding protein (B. Gao, M. S. Spector, and G. Kunos, J. Biol. Chem. 270:5614-5619, 1995). This protein, detectable in Southwestern (DNAprotein) blots of crude nuclear extracts as 32-and 34-kDa bands, has been purified 6,000-fold from rat livers by DEAE-Sepharose, heparin-Sepharose, and DNA affinity chromatography. Sodium dodecyl sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 56 publications
(79 reference statements)
1
48
0
Order By: Relevance
“…Studies of adrenergic receptor expression in the liver show that, based on the proliferative state of the hepatocyte, alphaand beta-adrenergic GPCRs are differentially expressed. 31,32 Similar changes in adrenergic receptor expression are observed when hepatocytes are placed into primary culture. The expression of multiple other proteins, such as the Ntcp bile acid transporter, cytochrome P450 enzymes, also changes during the primary culture of hepatocytes and in established cell lines.…”
Section: Discussionmentioning
confidence: 55%
“…Studies of adrenergic receptor expression in the liver show that, based on the proliferative state of the hepatocyte, alphaand beta-adrenergic GPCRs are differentially expressed. 31,32 Similar changes in adrenergic receptor expression are observed when hepatocytes are placed into primary culture. The expression of multiple other proteins, such as the Ntcp bile acid transporter, cytochrome P450 enzymes, also changes during the primary culture of hepatocytes and in established cell lines.…”
Section: Discussionmentioning
confidence: 55%
“…The mixtures were analyzed by DNA gel mobility shift assay using 32 P-labeled oligo II as a probe. 1 MF-2 Cells, Respectively-Our previous data showed that NF1/L, NF1/Red1, and NF1/X were able to activate transcription via the P2 promoter to more or less the same degree in Hep3B cells as in primary cultured hepatocytes (8). We wondered whether these NF1 isoforms can also regulate the P2 promoter activity in DDT 1 MF-2 smooth muscle cells.…”
Section: Methodsmentioning
confidence: 99%
“…Construction of Plasmids-The pNF1/X, pNF1/Red1, and pNF1/L expression vectors were prepared as described previously (8). The deleted NF1 expression vectors are prepared by subcloning the cDNAs encoding a set of truncated NF1 proteins into pcDNA3 expression vectors.…”
Section: Methodsmentioning
confidence: 99%
“…These genes lack any predicted perfect NFI dyad symmetric binding sites. While some mammalian promoters have been shown to contain functional hemi NFI binding sites (a single TTGGC or GCCAA site alone) (Cereghini et al, 1987;BoisJoyeux and Danan, 1994;Alonso et al, 1996;Gao et al, 1996), the absence of high-affinity dyad symmetric NFI binding sites within the myosin and exp-2 genes raises the possibility that they may not be direct targets of NFI.…”
Section: Fig 2 Amentioning
confidence: 99%